Microneedles: Physical enhancers for (trans)dermal drug delivery - Vučen Sonja; Bubić-Pajić Nataša; Savić Snežana; Vuleta Gordana (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2014)
The efficiency of(trans)dermal drug delivery has been severely reduced by the inability of most drugs to penetrate the skin at therapeutically useful rates. Recently, the use of micron-scale needles has been shown to increase skin permeability and significantly improve (trans)dermal drug delivery, particularly for macromolecules. Using the tools of the microelectronics industry and different materials, microneedles of various sizes and shapes have been fabricated. Due to their micron size (less than 300 μm in diameter and 50-900 μm in length), these needles do not reach the nerve endings in the dermis, providing a painless application, which is considered as their main advantage over hypodermic needles. Pathways created using microneedles are orders of magnitude bigger than molecular dimensions and, therefore, should readily permit transport of macromolecules, as well as possibly supramolecular complexes and microparticles Recently, in vivo studies have demonstrated a successful delivery of oligonucleotides, insulin, and many other drugs using a microneedles, as well as induction of the immune response from protein and DNA vaccines. Numerous studies conducted in this research field have led to launching the first microneedle-based (trans)dermal drug delivery systems on the market.